InGaN/GaN core/shell nanowires for visible to ultraviolet range photodetection. Issue 4 (19th January 2016) - Zhang, Hezhi; Messanvi, Agnès; Durand, Christophe; Eymery, Joël; Lavenus, Pierre; Babichev, Andrey; Julien, François H.; Tchernycheva, Maria
Abstract : We report on the fabrication and characterization of single nitride nanowire visible‐to‐ultraviolet p–n photodetectors. Nitride nanowires containing 30 InGaN/GaN radial quantum wells with 18% indium fraction were grown by catalyst‐free metal‐organic vapour phase epitaxy. Single nanowires were contacted using optical lithography. As expected for a radial p–n junction, the current–voltage ( I – V ) curves of single wire detectors show a rectifying behavior in the dark and a photocurrent under illumination. The detectors present a response in the visible to UV spectral range starting from 2.8 eV. The peak responsivity is 0.17 A/W at 3.36 eV. The on‐off switching time under square light pulses is found to be below 0.1 s.